Isu-Isu Kontemporer dan Strategi Pemasaran di SMKN 1 Kuripan dalam Menghadapi Era Digitalisasi - rahmadhani, Linda; Wahdiniwaty, Rahma; Favorit Makbul, Aktris Monika; Akhifin; Nurjaman, Maman (LPPM STIA Lancang Kuning Dumai, 2024)
This article discusses contemporary issues faced by SMKN 1 Kuripan, particularlyin the context of vocational education competition and digital-based marketingstrategies. This study employs a qualitative approach to analyze modern challengessuch as digitalization, changing labor market demands, and student productpromotion. The findings show that integrating digital media, marketing skilltraining, and collaboration with local SMEs are key to successful marketingstrategies at SMKN 1 Kuripan. In this context, digitalization not only enhancespromotion efficiency but also bridges the gap for students to understand modernmarketing practices. This article recommends further development in social mediautilization, advanced training, and student involvement in marketing processes asa form of experiential learning. By identifying opportunities and challenges, thisstudy contributes to providing insights for preparing vocational education to facethe continuously evolving digital era.